FORMULATION OF POLYMERIC NANOSUSPENSION CONTAINING PRAMIPEXOLE DIHYDROCHLORIDE AND HESPERIDIN FOR IMPROVED TREATMENT OF PARKINSON'S DISEASES - I, Somasundaram (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Aims and Objectives: The present study is to formulate the nanosuspension containing a hydrophilic drug pramipexole dihydrochloride and hesperidin and to increase the drug entrapment efficiency. Methods: Hesperidin and pramipexole dihydrochloride loaded in chitosan nanosuspension is prepared by ionic gelation method using chitosan and tripolyphosphate. There was no incompatibility observed between the drug and polymer through Fourier transform infrared and differential scanning calorimetric. Various other parameters such as particle size, zeta potential, scanning electron microscope, drug content, drug entrapment efficiency, and in vitro release have been utilized for the characterization of nanoparticles. Results and Discussion: The average size of particle is 188 nm; zeta potential is 46.7 mV; drug content of 0.364Â±0.25 mg/ml; entrapment efficiency of 72.8% is obtained with HPN3 formulation. The PHC1 shows the highest drug release followed by PHC2 due to low concentration of polymer and PHC4 and PHC5 show less drug release due to high concentration of polymer. The in vitro release of PHC3 is 85.2%, initial the burst release is shown which is approximately 60% in 8 h; then, slow release later on drastic reduction in release rate is shown in 24 h. The in vivo study histopathological report confers the effective protective against rotenone induces Parkinson's. Conclusion: PHC3 was chosen as the best formulation due to its reduced particle size and controlled release at optimum polymer concentration which may be used to treat Parkinson's disease effectively..